AFP level and histologic differentiation predict the survival of patients with liver transplantation for hepatocellular carcinoma - DEMİRBAŞ, BAHA TOLGA (My University, 2012)
BACKGROUND: In liver transplantation or resection for hepatocellular carcinoma (HCC), patient selection depends on morphological features. In patients with HCC, we performed a clinicopathological analysis of risk factors that affected survival after liver transplantation. METHODS: In 389 liver transplantations performed from 2004 to 2010, 102 were for HCC patients. Data were collected retrospectively from the Organ Transplantation Center Database. Variables were as follows: age, gender, preoperative alpha-fetoprotein (AFP) levels, Child-Pugh and MELD scores, prognostic staging criteria (Milan and UCSF), etiology, number of tumors, the largest tumor size, total tumor size, multifocality, intrahepatic portal vein tumor thrombosis, bilobarity, and histological differentiation. RESULTS: One hundred and two patients were evaluated. The 5-year overall survival rate was 56.5%. According to the UCSF criteria, 63% of the patients were within and 37% were beyond UCSF (P=0.03). Ten patients were excluded (one with fibrolamellary HCC and 9 because of early postoperative death without HCC recurrence), and 92 patients were assessed. The mean age of the patients was 56.5±6.9 years. Sixty-two patients underwent living donor liver transplantations. The mean follow-up time was 29.4±22.6 months. Fifteen patients (16.3%) died in the follow-up period due to HCC recurrence. Univariate analysis showed that AFP level, intrahepatic portal vein tumor thrombosis, histologic differentiation and UCSF criteria were significant factors related to survival and tumor recurrence. The 5-year estimated overall survival rate was 62.2% in all patients. According to the UCSF criteria, and the 5-year overall survival rate was 66.7% within and 52.7% beyond the criteria (P=0.04). Multivariate analysis showed that AFP level and poor differentiation were independent factors. CONCLUSIONS: For proper patient selection in liver transplantation for HCC, prognostic criteria related to tumor biology (especially AFP level and histological differentiation) should be considered. Poor differentiation and higher AFP levels are indicators of poor prognosis after liver transplantation.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Gastroenterology; Hepatology; liver transplantation; hepatocellular carcinoma; alpha-fetoprotein; GAMMA-CARBOXY PROTHROMBIN; SELECTION CRITERIA; TUMOR SIZE; IMPACT; CIRRHOSIS; RESECTION; MULTICENTER; RECURRENCE; INVASION; liver transplantation; hepatocellular carcinoma; alpha-fetoprotein